Policy on the Use of Regional Development Information System Applications at Regional Development Agency, Bone Regency - Firman Hamzah; M. Awaluddin; Syaripa Aeni; Andi Asdar; Mega Erdawati; M. Luthfi Siraj (Program Pascasarjana Universitas Negeri Makassar, 2021)
The local government information system is an information system used by BAPPEDA to document, plan all regional development and regional finances that aim to increase and facilitate acceleration in the implementation of supervision and evaluation of BONE Regency government public servants. has not been implemented properly, for example, some menus cannot be opened, the application of applications that seem rushed in its application, and lack of training in operating the SIPD application. used is descriptive research using a qualitative approach. The results of the study indicate that the Regional Development Information System (SIPD) has enormous benefits in preparing development budgets and planning because it contains all development and financial plans in every region in Indonesia.